The Role of the Government Tenders and Procurement Law in Combating Administrative Corruption - Ameerah Dhafer Hzam Alasmari; Nada Balto (International Journal of Law Research and Studies, 2025)
This study examines the legal framework for combating administrative corruption in the field of government tenders and procurement in Saudi Arabia. It analyzes the fundamental principles established by the system, such as transparency and disclosure, equality and fair competition, protection of the public interest, and oversight as a tool to limit abuse of authority. The study also highlights the obligations of the administration and the legal liability arising from violations. The findings show that these principles serve as preventive mechanisms against administrative corruption; however, practical implementation reveals certain gaps that may undermine their effectiveness. The study concludes that strengthening institutional oversight, improving the legal provisions, and enhancing the efficiency of procurement personnel are among the key recommendations to ensure integrity and efficiency in the management of public funds.
Keywords: Administrative Corruption; Government Tenders and Procurement Law; Legal Responsibility; Integrity